COMPARATIVE STUDY OF MINERAL COMPOSITION OF CATNIP HERB (NEPETA CATARIA L.) FROM DIFFERENT REGIONS - I. I. Terninko (Разработка и регистрация лекарственных средств, 2019)
The results of comparative study of the mineral composition by the inductively coupled plasma-atomic emission spectrometry method of catnip herb (Nepeta cataria L.) which growing on the territory of the Leningrad Region and the Belgorod Region are presented. 16 and 18 elements were found in the herb from the Leningrad and Belgorod regions, respectively, with the maximum content of Ca, Mg, K, Fe and Al, which can be considered as the main mineral elements of this plant. The accumulation and distribution of Cu, Mg, Na is defined as an additional chemical marker for herb catnip. The results obtained allow us to consider the catnip herb as a potential source of mineral elements.